Microenvironment-responsive peptide hydrogels: molecular mechanisms, design and frontiers - Ma, Xi-kun; Cao, Biao; Liu, Xi (Frontiers in Bioengineering and Biotechnology, 2025)
Responsive peptide hydrogels are advanced platforms for wound management because they can dynamically interact with the wound microenvironment. These smart materials respond to specific biochemical cues such as pH, reactive oxygen species (ROS), matrix metalloproteinases (MMPs), and glucose (Glu), enabling precise control over drug release, enhancement of cellular repair, and suppression of infection. By adapting to pathological conditions like elevated pH, persistent oxidative stress, and enzymatic imbalances, peptide hydrogels promote efficient healing in chronic wounds. Recent advances have expanded their responsiveness to include physical stimuli like temperature, light, and magnetic fields, broadening their applicability in deep and complex wound treatments. Despite promising outcomes, challenges remain in optimizing biocompatibility, biodegradability, and stimulus precision. Future efforts will focus on developing multifunctional and personalized hydrogel systems to achieve smarter, minimally invasive therapeutic strategies for wound care and beyond.